Sales of Consumer Chemicals in Zero-packaging Stores - a Challenge for Small and Medium-sized Chemical Companies - Branská, Lenka; Paták, Michal; Hromadníková, Kateřina; Pecinová, Zuzana (Univerzita Hradec Králové, 2021)
One of the innovations in the area of increasing the sustainability of packaging may be the introduction of zero-packaging sales. The paper deals with the advantages and disadvantages of zero-packaging sales, in relation to consumer chemicals. It presents the results of primary quantitative research carried out with 100 final consumers through electronic surveys using a structured questionnaire. Content analysis and multiple response analysis were used to identify the most significant advantages and disadvantages of purchasing consumer chemicals in zero-packaging stores. The biggest advantages are the reduction of waste from packaging materials, being able to buy the exact quantity required, and environmental protection. The biggest disadvantages include the insufficient expansion of the stores, the necessity to carry their own containers and the higher price of products sold. The advantage of "selling quality products" and the disadvantages of "uncertainty in terms of composition and quality" and "hard-to-observe hygiene requirements" are perceived differently depending on whether or not customers actually buy consumer chemicals in zero-packaging stores. The conclusions are important in terms of the possibility of creating a competitive advantage of small and medium-sized companies.
Prodej výrobků spotřební chemie v bezobalových prodejnách – výzva pro malé a střední chemické podniky
Keywords: sustainable supply chain; retail; zero-packaging; chemical product; udržitelné balení; spotřební chemie; bezobalový prodej